A New Age in Molecular Diagnostics for Invasive Fungal Disease: Are We Ready? - Kidd, Sarah E.; Chen, Sharon C.-A.; Meyer, Wieland; Halliday, Catriona L. (Frontiers in Microbiology, 2020)
Invasive fungal diseases (IFDs) present an increasing global burden in immunocompromised and other seriously-ill populations, including those caused by pathogens which are inherently resistant or less susceptible to antifungal drugs. Early diagnosis encompassing accurate detection and identification of the causative agent, and of antifungal resistance is critical for optimum patient outcomes. Many molecular-based diagnostic approaches have good clinical utility although interpretation of results should be according to clinical context. Where an IFD is in the differential diagnosis, panfungal PCR assays allow the rapid detection/identification of fungal species directly from clinical specimens with good specificity; sensitivity is also high when hyphae are seen in the specimen including in paraffin-embedded tissue. Aspergillus PCR assays on blood fractions have good utility in the screening of high- risk haematology patients with high negative and positive predictive values of 94% and 70%, respectively when two positive PCR results are obtained. The standardisation, and commercialisation of Aspergillus PCR assays has now enabled direct comparison of results between laboratories with commercial assays also offering the simultaneous detection of common azole resistance mutations. Candida PCR assays are not as well standardised with the only FDA-approved commercial system (T2Candida) detecting only the five most common species; whilst the T2Candida outperforms blood culture in patients with candidaemia, its role in routine Candida diagnostics is not well defined. There is growing use of Mucorales-specific PCR assays to detect selected genera in blood fractions. Quantitative real-time Pneumocystis jirovecii PCRs have replaced microscopy and immunofluorescent stains in many diagnostic laboratories although distinguishing infection may be problematic in non HIV-infected patients. For species identification of isolates, DNA barcoding with dual loci (ITS and TEF1α) offer optimal accuracy whilst next generation sequencing technologies offer highly discriminatory analysis of genetic diversity including for outbreak investigation, and for drug resistance characterisation. Advances in molecular technologies will further enhance routine fungal diagnostics.